Kebijakan Fiskal dan Peran Negara dalam Mewujudkan Keadilan Sosial Ekonomi Pancasila: Fiscal Policy and the Role of the State in Realizing Pancasila Socio-Economic Justice - Anggun Nabillah Sunarno Putri; Qurrotul 'Aini Sulha; Tyas Azzahra; Muhammad Hasan Hafidz (Litera Academica Publishing, 2025)
This article discusses the Pancasila economic system in relation to social justice and the challenges posed by global neoliberalism. The Pancasila economic system places humans as the subjects of development, emphasizing the principles of kinship, mutual cooperation, and sustainability in managing resources. Its primary goal is to achieve common prosperity and reduce social inequality. In contrast, global neoliberalism tends to emphasize free market mechanisms that often overlook aspects of social justice. Through a literature review and policy analysis, this article identifies government strategies to achieve social justice, including: strengthening the state's role in resource distribution, empowering cooperatives and small-medium enterprises, enhancing social protection for vulnerable groups, and promoting national economic sovereignty amidst globalization. This article concludes that implementing the Pancasila economic system requires a strong commitment from the government and active participation from society to become a fair and sustainable alternative in the era of global neoliberalism.